Ludwisarze pogranicza śląsko-łużyckiego Georg Wield I i Georg Wield II oraz ich działalność na przełomie XVI i XVII wieku - Poźniak, Michał (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
The paper introduces the readers to activities of a family of bell-founders – the Wields, who lived on the Silesian–Lusatian–Bohemian borderland at the turn of 16th and 17 th century. Campanological research concerning Lower Silesia has been rather poor to date, which results in a need for broader studies regarding historic bells and bell-founders
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne